Nyalep Narjhe Wedding Tradition in Bindang Village, Pasean District, Pamekasan Regency - Hanafi (Fakultas Syariah IAIN Madura, 2023)
Marriages between indigenous peoples with one another, between one tribe with another, between Muslims with one another, as well as there are differences in urban and village marriage customs. Customs that have become customary law will be more difficult and stronger because violations of them will meet a sanction according to the regulations that are enforced and obeyed in society, from here the custom is not just an ancestral heritage but becomes a rule that must be obeyed as happened in Bindang Village, Pasean District, Pamekasan Regency, it is forbidden for a younger brother to get married before his older sister, even though the younger brother is physically and mentally ready to marry. This is not allowed, because if this happens according to the prevailing belief and it is believed that a disaster will occur to the household that will be fostered and the family, especially the older brother he is stepping on. The results of the study were to prove whether the customs regarding the marriage of Nyalep Narjhê (preceding his older sister) in Bindang Village, Pasean District, Pamekasan Regency did not conflict with the actual demands and teachings of Islam, and whether it was considered fair for a younger sister who would marry first to crawl under a brother three times, so that this is no longer a continuous dark history.